Simultaneous Differentiation of the N1 to N9 Neuraminidase Subtypes of Avian Influenza Virus by a GeXP Analyzer-Based Multiplex Reverse Transcription PCR Assay - Luo, Sisi; Xie, Zhixun; Huang, Jiaoling; Xie, Zhiqin; Xie, Liji; Zhang, Minxiu; Li, Meng; Wang, Sheng; Li, Dan; Zeng, Tingting; Zhang, Yanfang; Fan, Qing; et al. (Frontiers in Microbiology, 2019)
To date, nine neuraminidase (NA) subtypes of avian influenza virus (AIV) have been identified in poultry and wild birds. Rapid and effective methods for differentiating these nine NA subtypes are needed. We developed and validated a rapid, sensitive, and robust method utilizing a GeXP analyzer-based multiplex RT-PCR assay and capillary electrophoresis for the simultaneous differentiation of the N1 to N9 subtypes in a single-tube reaction. Ten pairs of primers–nine subtype-specific pairs and one pan-AIV pair–were screened and used to establish the GeXP multiplex RT-PCR assay. A single subtype was detected using the developed GeXP assay; the N1 to N9 AIV subtypes individually generated two target peaks: the NA subtype-specific peak and the general AIV peak. Different concentrations of multiplexed subtypes were tested with this GeXP assay and the peaks of the corresponding NA subtypes were generated, suggesting that this GeXP assay is useful for identifying NA subtypes in mixed samples. Moreover, no peaks were generated for other important avian viruses, indicating negative results and validating the lack of cross-reactions between AIV subtypes and other avian pathogens. RNA templates synthesized through in vitro transcription were used to analyze the sensitivity of the assay; the limit of detection was 100 copies per reaction mixture. The results obtained from clinical samples using this GeXP method were consistent with the results of the neuraminidase inhibition (NI) test, and the ability of the GeXP assay to identify mixed infections was superior to amplicon sequencing of isolated viruses. In conclusion, this GeXP assay is proposed as a specific, sensitive, rapid, high-throughput, and versatile diagnostic tool for nine NA subtypes of AIV.